THE NATIONAL BIBLIOGRAPHY AS A REFLECTION OF THE DOCUMENTARY HERITAGE - Bliūdžiuvienė, Nijolė (Knygotyra, 2017)
The subject of this article is to analyze the national bibliography as a means for promoting the documentary heritage and providing access to it. It discusses various forms of the national bibliography as well as their potential for preserving the memory and ensuring access to documentary resources and their promotion. The article serves the purpose, by drawing on the analysis of foreign publications, of substantiating the idea that the national bibliography as a structured registry of the national publishing output may serve as a reliable means for promoting the documentary heritage. The article elaborates on the evolution of the notion and coverage of the national bibliography as well as its presentation to the public. The national bibliography was defined in the 60ies of the 20th century by joint efforts of UNESCO and IFLA. This definition underlined that the national bibliography must cover the nation’s entire published output. The notion of the national bibliography underwent some evolution, and in the 21st century the focus shifted towards registering electronic publishing resources alongside with solving the issues of presenting the national bibliography to the public. Previously, the presence of a bibliographic record in the national bibliography signified that the resource was available within the legal deposit collection of the library, whereas at present the issue of having to register national information resources which do not belong to this collection is gaining persistence. Another significant issue in making the national bibliography a comprehensive registry of the nation’s publishing output is the relation between the national bibliography and legal deposit. Successful and sustainable development of the national bibliography requires cooperative effort in creating and updating publication and factual data and efficient communication with publishers and other suppliers of public information within the chain of legal deposit. This interaction substantiates the existence of the national bibliography as the all-reflecting mirror creating opportunities to cognize the national documentary cultural heritage and ensuring its promotion and access, The register of bibliographic and authority data of published documents helps preserve the cultural and historical memory; ensures dissemination of knowledge about historical and cultural events and their interpretation; and gives a panorama of the cultural history, the heritage of the traditional culture, prominent fellow-countrymen and national uniqueness. The analysis of websites of national libraries of various countries which are legal deposit receivers shows that some of them remind the publishers of their obligation to submit legal deposit copies in a laconic manner and some of them provide more information, e.g. types and quantity of legal deposit copies and terms of submission as well as give references to appropriate legal acts. Some of these institutions highlight the significance of legal deposit as a means of preserving cultural heritage and ensuring access to it for the general public and researchers. However, there is no clear message addressed to the integral and primary chain of the legal deposit system, the publishers, about their responsibility about the comprehensiveness of legal deposit and the publishers’ benefits from contributing to the preservation and access of the national cultural heritage. The article analyzes the transformation of the national bibliography from a printed list to a presentation of linked data. Digital and information technologies applied in publication processes and creation of new forms of disseminating data of national bibliographies contribute to promoting the national history and cultural memory. Broad access to national bibliographic data allows the general public creating new services and products. The precise definition of purposes of the national bibliography and its users could facilitate the shaping of the appropriate model of the national bibliography.
Keywords: national bibliography; resources of national bibliography; legal deposit; the country’s publishing output; national bibliographic control; national bibliography service